Research of Soil and Water Conservation Effects of Production and Construction Projects Based on AHP-fuzzy Comprehensive Evaluation Method - Tai Hui; Wang Ping; Jiang Ning; Zhang Maolin; Xu Cong; Yang Zhenqi (Shuitu baochi tongbao, 2023)
[Objective] The soil and water conservation effects of production and construction projects implemented during the construction period were determined in order to provide data support for the follow-up supervision and management of soil and water conservation of hydropower stations, and to provide a reference for the evaluation of soil and water conservation effects of production and construction projects. [Methods] The study was conducted at the production and construction project of the Lawa hydropower station in the Xizang Autonomous Prefecture of Garze, Sichuan Province. The system framework consisted of the focal points and technical regulations of soil and water conservation monitoring of production and construction projects. The analytic hierarchy process (AHP) and fuzzy comprehensive evaluation were applied to establish a soil and water conservation effect evaluation system that included 14 indicators from five aspects (red line disturbance, soil and water loss control, greening restoration, implementation of soil and water conservation measures, and soil and water loss hazards) to comprehensively evaluate the water and soil conservation effect during the construction period of the Lawa hydropower station. [Results] The comprehensive evaluation indexes of the Lawa hydropower station during 2017—2021 were 0.840 (excellent), 0.727 (good), 0.571 (average), 0.786 (good), 0.792 (good), respectively, indicating a trend of decreasing first and then increasing. The overall result was good. [Conclusion] Soil and water conservation work performed during the construction of the Lawa hydropower station (including red line disturbance, soil and water loss control, greening restoration, implementation of soil and water conservation measures, and soil and water loss damage) performed well overall, and achieved good benefits.